Clinical and genomic features of adult and paediatric acute leukaemias with ophthalmic manifestations. Issue 1 (3rd October 2019) - Skarsgård, Lisa Stenman; Andersson, Mattias K.; Persson, Marta; Larsen, Ann-Cathrine; Coupland, Sarah E.; Stenman, Göran; Heegaard, Steffen
Abstract : Objective: To describe the clinicopathological and genomic features of nine patients with primary and secondary orbital/ocular manifestations of leukaemia. Methods: All orbital/ocular leukaemic specimens from 1980 to 2009 were collected from the Danish Register of Pathology. In six cases, medical records and formalin-fixed, paraffin-embedded blocks were available. Three cases from the Department of Pathology, Royal Liverpool University Hospital, were also included. Immunophenotypes and MYB oncoprotein expression were ascertained by immunohistochemistry. Genomic imbalances were analysed with comparative genomic hybridisation arrays and oncogene rearrangements with fluorescence in situ hybridisation. Results: Four patients had B-cell precursor acute lymphoblastic leukaemia (BCP-ALL) and five had acute myeloid leukaemia (AML). Two patients with BCP-ALL and one with AML had primary orbital manifestations of leukaemia. Common symptoms were proptosis, displacement of the eye, and reduced eye mobility in patients with orbital leukaemias and pain, and reduced visual acuity in patients with ocular leukaemias. All patients with primary orbital lesions were alive up to 18 years after diagnosis. All but one patient with secondary ophthalmic manifestations died of relapse/disseminated disease. ETV6 and RUNX1 were rearranged in BCP-ALL, and RUNX1 and KMT2A in AML. Genomic profiling revealed quiet genomes (0–7 aberrations/case). The MYB oncoprotein was overexpressed in the majority of cases. Conclusions: Leukaemias with and without ophthalmic manifestations have similar immunophenotypes, translocations/gene fusions and copy number alterations. Awareness of the clinical spectrum of leukaemic lesions of the eye or ocular region is important to quickly establish the correct diagnosis and commence prompt treatment.